Análisis de la movilidad de estudiantes y funcionarios hacia y en el campus central del Instituto Tecnológico de Costa Rica - Moya-Mora, Ana Lucía (Instituto Tecnológico de Costa Rica, 2017)
Proper transportation planning is one of the biggest challenges that cities are facing today. In Costa Rica, the lack of transportation planning has caused a series of environmental, social and economic challenges. The central campus of the Technological Institute of Costa Rica is beginning to show the first symptoms of lack of transportation planning: traffic congestion at peak hours and saturation of parking spaces. This research carried out an analysis of the mobility of students, professors and administrative staff towards the campus, as well as the behavior of the mobilizations in the accesses of the campus. Information was collected through surveys, traffic counts of pedestrian, cyclists and vehicles and an analysis of the existing infrastructure. The research found that the mobilization patterns of the population are quite stable, that the majority of the population moves by using sustainable modes (bus, bicycle and walking) and it was determined that if measures are not taken to improve the sustainable modes of mobilization and discourage private transport, it is possible that the motorization rate in the institution will increase over time. A roadmap for the implementation of an Institutional Mobility Plan was designed, which includes key recommendations to increase the mobility using active and low emissions transportation modes. Finally, this study establishes a robust baseline of the mobilization of students, professors and administrative staff of the central campus of the Technological Institute of Costa Rica on the II semester of 2016. Also it is a replicable method for continuously monitoring mobility and transportation.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2017.
Keywords: Sostenibilidad; Universidad; Cambio; Transporte; Planificación